Teaching and Learning Support for Computer Architecture and Organization Courses Design on Computer Engineering and Computer Science For Undergraduate: A Review - Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Understanding computer system hardware is basic for the undergraduate student which study in the computer area. System user always needs a faster, cheap and reliable process which is conducted by it computer system self. To fulfill that process is required how a computer works from their design and how they operate. That course is conducted by Computer Architecture and Organization (CAO) course. Two computer undergraduate  area  which  studies  CAO  is  Computer Engineering (CE) and Computer Science (CS). To support great learning at CAO both CE and CS needs to not just study which has a material course but they had to practically study computer architecture  and  design  by  the  simulator.  Why  simulator  is chosen, because to create computer such as CPU, RAM etc. needs big  systems that  can  manufacture them.  Nowadays too  much freely available simulator that can be downloaded and used anytime, but not all simulators meet study requirements and didn’t meet the CAO Learning Outcome. CS and CE have an international curriculum that given by ACM Computing Curricula. So this paper is discussed what kind of simulator that meets   Computing   Curricula   requirement   to   implement   at learning process which helps the instructor to choose simulator